Lymphoma - Tutar, Yusuf (IntechOpen, 2022)
Lymphoma is a group of malignant diseases caused by the clonal proliferation of lymphocytes. Current treatment options include chemotherapy, radiotherapy, and bone marrow/stem cell transplantation. Development of new treatment options for cancer medications include small molecules and monoclonal antibodies for immunotherapy. In addition, the discovery of new phytochemical agents used in complementary and alternative medicine adds perspective to the treatment of lymphoma. This book highlights recent developments in the treatment of lymphoma. Chapters discuss different types of lymphomas, such as follicular lymphoma, gastrointestinal lymphoma, splenic B-cell lymphoma, and others, as well as the available treatment options for each.